Semantic rule-guided three-dimensional reservoir modeling method using an improved multiple-point geostatistics simulation - Chen, Qiyu; Li, HuanHuan; Xun, Lei; Chen, Dajie; Fang, Hongfeng; Liu, Gang (Frontiers in Earth Science, 2026)
PurposeTo overcome the reliance on manual parameter adjustment and the difficulty in uncertainty quantification of traditional Multiple-Point Geostatistics (MPS) methods, and to address the general lack of geological semantic rule utilization that limits the reliability of existing 3D reservoir models.MethodsA 3D reservoir modeling method integrating semantic rule guidance and MPS simulation is proposed. Geological semantic rules for sequence stratigraphy and fault kinematics were incorporated into the structural modeling workflow. Subsequently, an MPS algorithm featuring automatic domain kernel function selection and a rapid dual-dimensional parameter optimization strategy was employed for lithofacies and property simulation.ResultsExperimental results show that the models constructed by the proposed method not only maintain geological semantic consistency and coherence but also accurately characterize the spatial distribution of lithofacies and properties in the study area.ConclusionThis method effectively integrates semantic rules with an optimized MPS workflow, enhancing the geological reliability and representational accuracy of 3D reservoir models for improved reservoir characterization.